Efforts to Improve Student Learning Outcomes in Learning Indonesian History Using The Project Based Learning (PjBL) Model With the TPACK Approach in Class XI – 10 of SMA Negeri 14 Medan Academic Year 2024/2025 - Sitanggang, Nicky Johanes; Diansyah, Arfan; Gultom, Imelda Megawati (LPPPI Publishing, 2024)
Offering history subjects to pupils can cultivate their critical, logical, and imaginative thinking skills. However, in actuality, students at SMA Negeri 14 Medan encounter challenges in their history learning endeavours. Researchers conducted a study to enhance student learning outcomes in Indonesian History by focussing on the topic of Early Challenges of Independence during classroom instruction. The research sample included of 36 students from classroom XI-10 at SMA Negeri 14 Medan. The data collection method employed was the administration of a written test in the form of multiple-choice questions, which participants responded using the Wordwall web platform. The data analysis methodology employed in this study involved the utilisation of percentage analysis, namely by comparing the original conditions with the outcomes obtained in each iteration. The research findings indicate that implementing the Project Based Learning (PjBL) instructional model with the Technological Pedagogical Content Knowledge (TPACK) approach in the Indonesian History curriculum, specifically focussing on the topic of Early Challenges of Independence, leads to enhanced student learning outcomes. The conclusion of this study confirms that the action hypothesis has been addressed. Specifically, the implementation of the Project Based Learning (PjBL) instructional model with the Technological Pedagogical Content Knowledge (TPACK) approach has resulted in improved student learning outcomes in the field of Indonesian History. The subject of XI- 10 is being taught in Class XI at SMA Negeri 14 Medan during the academic year 2024/2025.